Kestabilan emulsi dan oksidasi low fat mayonnaise menggunakan kefir sebagai alternatif emulsifier - Herly Evanuarini; Nurliyani Nurliyani; Indratiningsih Indratiningsih; Pudji Hastuti (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2019)
Mayonnaise is popular sauce. It’s kind of semi solid oil in water (o/w) emulsion which containing oil, acidifier and pasteurized egg yolk as an emulsifier. The consumers have demanded that for natural, healthy, and low calorie food especially for development and manufacture of low fat mayonnaise. The common emulsifiers are egg yolk, casein, and whey. Kefir can replace egg yolk to develop low fat mayonnaise. The use of egg yolk be reduced and kefir was used to develop a low fat mayonnaise as emulsifier replacer to egg yolk. The purpose of this research attempts to observe the emulsion stability, antioxidant, and oxidation stability of low fat mayonnaise prepared using rice bran oil and kefir during storage. The research methods using experimental design. The result shows the addition of kefir can create low fat mayonnaise by increasing emulsion stability.